The Impact of DER, TATO and Company Size on ROE - Annisa Annisa; Mega Sherlina Setiawan (CAKRAWALA : Management Science Journal, 2025)
The research method used is descriptive statistical analysis using secondary data in the form of financial statements for the period 2020 – 2023 on the Indonesia Stock Exchange.  The sampling technique uses the purposive sampling method. The research population is 50 companies and the sample used is 13 companies in IDX Quality 30. The data analysis used was multiple linear regression analysis. The results of the study partially showed that the Debt Equity Ratio had a positive effect on the Return On Equity variable, Total Asset Turn Over had no significant effect on  the Return On Equity variable  and the measure had a significant effect on  the Return On Equity variable  while the results of the simultaneous study showed that  the Debt Equity Ratio, Total Asset Turn Over variables and Size have a significant effect on the Return On Equity variable.